Prospects of Phytochemicals as Antimicrobial Growth-Promoters for Poultry Feed - Ruth, T. S. Ofongo (Research Aspects in Agriculture and Veterinary Science Vol. 5, 2022)
Utilization of phytogenics or extracts of plants as suitable alternative to antimicrobial growth promoters has yielded quiet interesting results of which several reported primary data elucidating their positive benefits exist. Issues of gastrointestinal health and limiting mortality in the absence of in-feed antibiotics is a core concern to most poultry farmers. As a result, the antimicrobial prospective of phytochemicals from medicinal plants and their potential to maintain health thereby minimizing sub-clinical bacteria-induced zoonotic enteropathogenic infections in poultry birds cannot be over-emphasized. Vernonia amygdalina (Bitter leaf) and Azadirachta indica (Neem) leaves were collected fresh and oven dried to 15% moisture content. Phytochemical analysis of their methanol extract obtained by cold maceration was carried out using appropriate method required for each phytochemical determined. The qualitative and quantitative analysis of each respective extract was carried out separately. Qualitative analysis indicated that saponins and terpenoids were highly detected (+++) in V. amygdalina and slightly detected (+) in A. indica. Phenolic compounds were highly detected (+++) in both plants while tannins were highly detected only in A. indica. Flavonoids were detected (++) in both plants, Quantitative analysis of V. amygdalina revealed a rather high concentration of complete phenolic content and overall flavonoid content. Total phenolic content of 44.76 mg Gallic acid equivalent / g of extract and 57.21 mg Rutin equivalent / g of extract (total flavonoid content) was recorded in V. amygdalina and 25.77 mg Gallic acid equivalent / g of extract (total phenolic content) and 24.45 mg Rutin equivalent /g of extract (total flavonoid content) in A. indica. In – vivo primary data showed the prospective of both plants to modulate gut bacteria population towards beneficial bacteria (Lactobacillus) over pathogenic bacteria (Salmonella spp and Escherichia coli). In-vitro and in-vivo primary data from broiler studies with aqueous extract of bitter leaf and neem leaf elucidated the antimicrobial growth promoter prospective of their phytochemicals.